The Humanities in Jesuit Schools 1548–1773 - Grendler, Paul F. (Journal of Jesuit studies, 2024)
The humanities were the most important part of Jesuit education. The Jesuit lower school taught grammar, humanities, and rhetoric to boys and young men in the Society of Jesus and it was free. The goal was to educate boys in the humanities so that they would become adult leaders who would make wise decisions for the common good. Most Jesuit schools were small. Enrollment information for classes in the province of Milan in 1661 offers an example. About seventy-five percent of students in Jesuit schools attended the lower school classes. The Ratio studiorum of 1599 prescribed a humanities curriculum that focused on Golden Age ancient authors especially Cicero and Virgil. However, Jesuit schools did not follow the Ratio studiorum strictly in the seventeenth and eighteenth centuries. They taught baroque Latin. They taught vernacular languages. They taught little Greek. But they retained the core of the Ratio studiorum.